Palladium-Catalyzed C(sp2)–H Silylation via a Native-Amine-Directed Strategy - Yan, Yintao; Wang, Xuan; Li, Jianhua; Jiang, Chao (Synlett, 2022)
A palladium-catalyzed C(sp2)–H silylation of morpholinones to afford silyl morpholinones is reported. The native secondary amine, which is tolerated in the reaction, is able to promote the C–H activation and silylation of the aryl group. The substrates are monosilylated selectively and tolerate various functional groups. The resulting silyl morpholinone derivatives are potentially useful in pharmaceuticals and agrochemicals.
Keywords: palladium; C–H activation; C(sp2)–H Silylation; morpholinone; organosilicon compounds